Hubert Butler's Nonpresence in Croatia - Grgas-Mufa, Stipe (Array, 2014)
The article examines the strange non-reception of H. Butler in Croatia considering the fact that he wrote about its history and people. The author proposes a number of explanations for this non-presence and proposes that not only ought Butler to be incorporated in the Croatian archive of cross-cultural readings of Ireland but that this site opens a way to think through the similarities and differences between the tow countries.